Authors, Publishers and Readers of Popular Literature in Latvia in the Late 1980s and Early 1990s - Jana Dreimane (Interlitteraria, 2015)
The purpose of the present article is to determine changes in book publication and reading habits in Latvia from the end of the 1980s onwards – a period characterized by the gradual shrinkage of the dictate of state authorities and political censorship, Latvia regaining independence in 1990 and the first years of the independent republic (up to 1995) involving the transition from the centrally planned economy to the free market economy, when the publishing houses which were established in Soviet times made attempts to pursue new development paths, whereas the newly-established ones tried to put down their roots in the publishing business.